2012
DOI: 10.1007/s00436-012-2871-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of alpha lipoic acid combined with praziquantel on liver fibrosis induced by Schistosoma mansoni challenged mice

Abstract: Schistosomiasis is an endemic disease in 74 countries causing more than 250,000 deaths every year. Accordingly, the development of an effective drug for eradication of schistosomiasis is an open research field. The current chemotherapy for control is praziquantel (PZQ). However, PZQ does not improve liver fibrosis. Therefore, the aim of this study is to evaluate the combined effect of alpha lipoic acid (ALA) with PZQ on the liver fibrosis induced by Schistosoma mansoni challenged mice. Evaluation was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
6
25
0
Order By: Relevance
“…Previous reports indicated that the reversibility of inflammation and liver fibrosis may be possible using PZQ treatment for schistosome infection in animal models (Abdel-Hafeez et al 2012;Huang et al 2011;Liang et al 2011;Mata-Santos et al 2010). We have also found that there was a significant decrease of granuloma size, reduction of liver, and spleen enlargement after killing adult worms (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous reports indicated that the reversibility of inflammation and liver fibrosis may be possible using PZQ treatment for schistosome infection in animal models (Abdel-Hafeez et al 2012;Huang et al 2011;Liang et al 2011;Mata-Santos et al 2010). We have also found that there was a significant decrease of granuloma size, reduction of liver, and spleen enlargement after killing adult worms (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Mean values of granuloma areas in every slaughtered period were used for statistical analysis. Detailed methodology of the hepatic histopathology and granuloma measurement could refer to previous literatures (Abdel-Hafeez et al 2012;Mata-Santos et al 2010). …”
Section: Observation Of Liver and Spleen Enlargementmentioning
confidence: 99%
“…Due to the warnings about drug resistance, possible infection recurrence, low efficacy in some cases and very restricted therapeutic alternatives, the search for new drug prototypes is a continuous challenge and must be encouraged in academia and the pharmaceutical industry. 6,7 In the past few years, the interest in natural products as a potential source for the treatment of parasitic diseases has grown. 8 The objective of these studies is to propose alternative methods for the treatment of these diseases, especially for neglected ones, such as schistosomiasis, 9 since this has left researchers on alert regarding the development of resistance to the only drug used for its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of S. mansoni infected mice with PZQ alone or in combination with CSE showed significant increase in SOD and catalase levels. Several studies found that PZQ diminishes oxidative stress in schistosomiasis by increasing antioxidant enzyme activities (Abdel-Hafeez et al, 2012;Rizk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%